May lakad kami ni tatay A trip with my father - Evasco, Eugene Y.; Sabas, Brent; Villalon, Mixkaela (Quezon City LG & M, 2013)
"This book reminds children the importance of exercise in having a healthy mind and body. It also introduces different models who may serve as examples in relation to fitness and active lifestyle."
Donated by Eugene Y. Evasco.
Para sa edad/For ages 5-8.
Text in Filipino and English.
Keywords: Exercise -- Juvenile literature; Physical fitness -- Juvenile literature; Father and child -- Juvenile literature